Deforestation for agriculture increases microbial carbon use efficiency in subarctic soils - Schroeder, Julia; Peplau, Tino; Pennekamp, Frank; Gregorich, Edward; Tebbe, Christoph C.; Poeplau, Christopher (Biology and Fertility of Soils, 2024)
Agriculture is likely to expand poleward with climate change, encouraging deforestation for agriculture in subarctic regions, which alters soil physical, chemical and biological properties and potentially affects microbial metabolic efficiency. Deciphering how and by which mechanisms land-use change affects microbial carbon use efficiency (CUE) will enable the development of mitigation strategies to alleviate C losses. We assessed CUE using 18O-labelled water in a paired-plot approach on soils collected from 19 farms across the subarctic region of Yukon, Canada, comprising 14 pairs of forest-to-grassland conversion and 15 pairs of forest-to-cropland conversion. Microbial CUE significantly increased following conversion to grassland and cropland. Land-use conversion resulted in a lower estimated abundance of fungi, while the archaeal abundance increased. Interestingly, structural equation modelling revealed that increases in CUE were mediated by a rise in soil pH and a decrease in soil C:N ratio rather than by shifts in microbial community composition, i.e. the ratio of fungi, bacteria and archaea. Our findings indicate a direct control of abiotic factors on microbial CUE via improved nutrient availability and facilitated conditions for microbial growth. Overall, this implies that to a certain extent CUE can be managed to achieve a more efficient build-up of stabilised soil organic C (SOC), as reflected in increased mineral-associated organic C under agricultural land use. These insights may also help constrain SOC models that generally struggle to predict the effects of deforestation, something that is likely to take place more frequently in the subarctic.